ANALISA DAN EVALUASI UNTUK PENGEMBANGAN FITUR APLIKASI XYZ (SEBUAH PENDEKATAN STUDI KASUS) - Sudiana, Sudiana; Nugroho, Alwin Ponco; Ridho, Muhammad Alif; Prawira, Timotius Christian (Infotech: Journal of Technology Information, 2019)
The purpose of this paper is analyze and evaluate the features of an XYZ application at PT. XYZ and develop features make easier for customers in invoicing, accounting, and inventory. Evaluation uses direct interview techniques to users and analysis using the Unified Modeling Language (UML) Diagram to visualize, design, and document features in the XYZ application. The results of this paper are develop features such as User Access Rights, Reminder via Email, Multi Location, Import & Export Data, and Advance Invoice Settings, which development provides more customer service to make it easier and more efficient when using applications XYZ.